If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -1(-24) = 12 Multiply -1 * -24 -4x + 24 = 12 Reorder the terms: 24 + -4x = 12 Solving 24 + -4x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -4x = 12 + -24 Combine like terms: 24 + -24 = 0 0 + -4x = 12 + -24 -4x = 12 + -24 Combine like terms: 12 + -24 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| f^2+9f-81=9f | | 1000.00+5000x=1200 | | 10z-2+9z-3-z=0 | | 1000.00+5000=1200 | | x^2+9x-7= | | 1/x-5/2=3/2 | | 3x=106-2y | | -15-2c+17-4c=0 | | 3n^2-7n=-2 | | 6v^2+24v-72= | | 3h^2+4h+1=0 | | -3(2n-5)=5 | | a^2-2a+12=0 | | 4(2b+2)-3=0 | | a^2-2a+10=0 | | 25x^2-36x^4=0 | | 3x+y+7=9x | | n(n+2)= | | 6q+5=2m+1 | | -3-(-15)=15 | | (4h+5)(h+7)=0 | | 2d+17-3-2d+4d=0 | | 0=(60000-1500x) | | x=(60000-1500x) | | 19=16y*21 | | c/2c^4 | | 8=11y-7 | | 3star=1x+16 | | -4+7z+3-2z=0 | | 6b^4/9b^5c | | 5x+4=124 | | 17x^2y^2+51x^4y= |